The Biography of Imam Al-Ghazali's Thought on Islamic Education and its Relevance to Contemporary Islamic Education - Anggun Putri Melati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Amid modernization, digitalization, and secular humanism, contemporary Islamic education faces a widening gap between intellectual achievement and moral-spiritual formation. Prior studies have examined isolated dimensions of Imam Al-Ghazali's educational thought, such as character formation or the balance of knowledge and faith, but few have systematically linked his biography with a thematic mapping of his pedagogical concepts and their present-day relevance. This study addresses that gap by examining Al-Ghazali's thought on Islamic education, tracing its formation through his biography, and assessing its contemporary relevance. Using a qualitative library research method, primary sources such as Ihya' Ulum al-Din and Ayyuha al-Walad were analyzed and synthesized. Findings show Al-Ghazali's pedagogy is a coherent, operational framework, integrating knowledge and practice with intellectual, moral, and spiritual dimensions, anticipating the fragmentation between academic competence and character formation still unresolved today. This holistic model offers a substantive solution for restoring moral direction to Islamic education amid globalization.